Digital Marketing Strategies among Traditional Healers in Solo and Wonosobo: Engaging Young Audiences - Yohanes Langgar Billy; Indiwan Seto Wahjuwibowo; Kanon Mommsen Wongkar (Jurnal Komunikasi dan Bisnis, 2025)
Traditional healers in Solo and Wonosobo face increasing challenges in engaging young people, despite the widespread use of digital platforms by this demographic. This study explores the adoption of digital marketing strategies by traditional healers to enhance their outreach to youth. Employing a qualitative approach, semi-structured interviews were conducted with healers in both regions to examine their current practices and perceptions regarding digital engagement. The findings reveal that while a few healers, such as Ibu Ani, have effectively utilized platforms like TikTok and Instagram, most still rely heavily on word-of-mouth promotion. Limited use of digital media stems from a lack of technological skills and insufficient content tailored to youth preferences. The study is guided by Uses and Gratifications Theory to understand how young people seek and interact with online health content. The results suggest that to improve engagement, traditional healers should adopt more interactive and youth-oriented digital strategies, including collaboration with influencers and the use of culturally resonant content. These findings offer practical insights for revitalizing traditional medicine in the digital age.